Few Things, many Times. Maths in CEIP San Isidoro (Journal of Parents and Teachers, 2018)
In this article, it will be described the change in Maths teaching methodology which was introduced in our school. The learning process is acquired by using manipulation, the use of other algorithms in maths operations, all with respectful methodologies for our students development. It will be also outlined how these changes have been achieved in the different classes in our maths workshop course.
Keywords: pre-school education; primary education; metodological change; manipulative maths; logical mathematical thinking; OAOA movenment; counter rods; experiences; research activity